Digital technologies for government -supported health insurance systems in Asia and the Pacific (Asian Development Bank, 2021)
Explores digital solutions that can support the core business processes of public health insurance operators in Asia and the Pacific. Examples from low- and middle-income countries in the region and beyond are drawn to demonstrate how digital solutions have improved health insurance management and administration.